PENGARUH MOTIVASI KERJA TERHADAP KINERJA PERANGKAT DESA DI KECAMATAN SUNGAI AMBAWANG - Magdalena Neni; Sukma Febrianti; Ishak Ishak (Jurnal Ekonomi STIEP, 2022)
The government is an organization that has the authority to regulate its territory by mobilizing human resources effectively and efficiently to serve the community. The fifteen villages in Sungai Ambawang Sub-district must have village officials who can work according to the demands of the job and must complete each worker on time with perfectly completion of work. This study aimed to determine and analyze the effect of work motivation on the performance of village officials in the Sungai Ambawang District. The population in this study was village apparatus, amounting to 75 people. In taking the sample, the researcher used a purposive sampling technique, where the sampling technique was determined by determining certain criteria. So the respondents who meet the criteria and can be used as samples amounted to 33 people. Data analysis using SPSS version 26 software, validity test, and reliability test. Then the conclusion is drawn using a simple linear regression statistical test and partially analyze the effect t-testt). Based on the results of the partial regression, statistically tcount 0.741 < from ttable 1.69552 and sig. 0.464 < from 0,05. This means that the work motivation variable has no significant effect on the performance of village officials. The value of R Square is 0.017. This means that the influence of the work motivation of village officials in Sungai Ambawang District on performance is 1.7% and the remaining 98.3% is influenced by other factors not observed in this study.